2013
DOI: 10.1016/s0924-9338(13)77435-2
|View full text |Cite
|
Sign up to set email alerts
|

2854 – Depression, anxiety and anger in patients with polycystic ovary syndrome

Abstract: Introduction: Polycystic Ovary Syndrome (PCOS) is a syndrome of heterogeneous nature, affecting multiple systems, particularly the endocrine system. We propose to investigate the possible relationships among hormonal changes, levels of anxiety, depression, and anger in patients with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Stapinska-Syniec et al (2018) found that 52% of 250 PCOS participants reported depressive symptoms. Significantly more women suffering with PCOS presented with severe anxiety, trait anger, and depression, compared with agematched healthy women (Erdem et al, 2013). Mood disorders among PCOS sufferers may enhance their disease burden, as those suffering from depression and anxiety may also present with significantly higher dehydroepiandrosterone sulfate (DHEAS) levels (Annagür et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stapinska-Syniec et al (2018) found that 52% of 250 PCOS participants reported depressive symptoms. Significantly more women suffering with PCOS presented with severe anxiety, trait anger, and depression, compared with agematched healthy women (Erdem et al, 2013). Mood disorders among PCOS sufferers may enhance their disease burden, as those suffering from depression and anxiety may also present with significantly higher dehydroepiandrosterone sulfate (DHEAS) levels (Annagür et al, 2013).…”
Section: Introductionmentioning
confidence: 99%